Unbundling returns to degrees and skills: Evidence from postsecondary education in Colombia - Matias Busso; Juan Sebastián Mu\~noz; Sebastián Monta\~no (Inter-American Development Bank (IDB), 2020)
This paper shows that returns to education are not enough to capture all the returns to human capital. Using longitudinal data of all college graduates in Colombia, we estimate labor market returns to postsecondary degrees and to various skillsincluding literacy, numeracy, foreign language, field-specific, and non-cognitive skills. Graduates of longer programs, of private institutions, and of schools with higher reputation earn higher wages. Even after controlling for all the characteristics of the degree, a one standard deviation increase in each skill predicts an average wage increase of two percent. Returns to skills vary along the wage distribution, with tenure, with the field of specialization and the type of job obtained immediately after graduation.
Keywords: I20; I24; J24; J31; 330; Returns to skills; Returns to education; Numeracy; Literacy; Foreign language; Specific skills; Non-cognitive; Colombia